2016
DOI: 10.1002/ptr.5624
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nociceptive Effect of Resveratrol During Inflammatory Hyperalgesia via Differential Regulation of pro-Inflammatory Mediators

Abstract: Sensitization of nociceptive neurons by inflammatory mediators leads to hypersensitivity for normal painful stimuli which is termed hyperalgesia. Oxidative stress is an essential factor in pathological pain; therefore, antioxidants qualify as potential anti-hyperalgesic agents. The present study examines the efficacy of the natural antioxidant resveratrol in complete Freund's adjuvant (CFA) induced hyperalgesic rats. Thermal hyperalgesia was measured at different time points by paw withdrawal latency test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Why the temperature-related moxibustion analgesic effect patterns were different on different pain model? The reason would be that CFA-induced chronic inflammatory pain model is sensitive to thermal stimulus [ 38 , 39 ], while SNI-induced neuropathic pain model is much sensitive to mechanical stimulus [ 32 , 40 , 41 ]. That was why we employed TWL to access CFA-induced inflammatory pain model while we selected MWL to evaluate SNI-induced neuropathic pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Why the temperature-related moxibustion analgesic effect patterns were different on different pain model? The reason would be that CFA-induced chronic inflammatory pain model is sensitive to thermal stimulus [ 38 , 39 ], while SNI-induced neuropathic pain model is much sensitive to mechanical stimulus [ 32 , 40 , 41 ]. That was why we employed TWL to access CFA-induced inflammatory pain model while we selected MWL to evaluate SNI-induced neuropathic pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Res possesses neuroprotective effects as well as improves the behavioral and pathological outcomes of diverse types of nerve injury, including traumatic brain injury, peripheral nerve injury, stroke, and spinal cord injury (Ates et al 2006;Singleton et al 2010;Girbovan et al 2012;Xu et al 2018). Res could also reduce peripheral sensitization by inhibiting inflammatory responses in nerves or local tissues (Singh and Vinayak 2016). Moreover, previous studies revealed that in the spinal cord, the anti-inflammatory effect of Res was associated with the suppression of glial activation (Yang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of probable reduction of mRNA IkBα expression under resveratrol in our study, a positive effect of resveratrol on levels of proinflammatory CK has been found out. In our opinion, inhibition of STAT1 or IRF-1 may also be one of the possible mechanisms of its action [26].…”
Section: Resultsmentioning
confidence: 92%